Cambios morfométricos en una laguna pampeana (Argentina) como consecuencia de la variabilidad pluviométrica (1960-2015) y sus posibles efectos sobre la comunidad íctica - Zunino, Josefina (2018)
The aim of this study was to analyze the pluviometric variability and its effects on the morphometric and limnological variations in the shallow lake of Puan (Argentina) in order to interpret the population dynamics of the specie Odontesthes bonariensis considering the alternation between wet and dry events, during the period 1960-2015. Standard Precipitation Index (SPI) and Quintiles method were applied in order to study the rainfalls behavior. Morphometric parameters were calculated from digital processing of LANDSAT 8 OLI-TIRS, while limnological variables were studied with samples taken in situ. Besides, data of the O. bonaerensis provided by the Ministry of Agrarian Affairs (Argentina) were analyzed. The results evidenced that the size and quantity of O. bonariensis have a significant correlation with the area. In addition, during 2013 the decrease of the area and the conductivity along with the increase in the water temperature and an intensive fishing occasioned critical condition in the ecosystem and currently the O. bonariensis is absent in this shallow lake. The results obtained in this study, represent a tool to establish sustainable management strategies on a shallow lake with recreational and touristic activities.